ANALYSIS OF FACTORS AFFECTING THE SUCCESS IN APPLYING ACCRUAL-BASES GOVERNMENT ACCOUNTING STANDARD WITH REGIONAL MANAGEMENT INFORMATION SYSTEM AS A MODERATING VARIABLE IN MEDAN MUNICIPAL GOVERNMENT - Surbakti, Agustina (Asosiasi Dosen Akuntansi Indonesia, 2018)
The objective of the research was to find out 1) the influence of Human Resources, Organizational Commitment, Communication, and Accrual-Based Manual on the Success in Applying Accrual-Based SAP (Government Accounting Standard) in Medan Municipal Government and 2) Regional Management Information System in moderating the correlation of Human Resources, Organizational Commitment, Communication, and Accrual-Based Manual with the Success in Applying Accrual-Based SAP in Medan Municipal Government. The research used causality method. The population was 57 SKPD (Regional Work Units) of Medan Municipal Government, and all of them were used as the samples (census sampling). Primary data were gathered by using survey method and distributing questionnaires to the respondents of each SKPD of Medan Municipal Government and analyzed by using Bayes method and interaction approach for moderating variable. The result of the research showed that 1) Human Resources, Organizational Commitment, Communication, and Accrual-Based Manual had positive and significant influence on the Success in Applying Accrual-Based SAP in Medan Municipal Government, and 2) Regional Management Information System could moderate the correlation of Organizational Commitment and Accrual-Based Manual, but it could not moderate the correlation of Human Resources and Communication with Applying Accrual-Based SAP in Medan Municipal Government.